Tri Hita Karana Values in Teaching and Learning of Indonesian Language for Foreign Students - Ida Bagus Artha Adnyana; I Ketut Sadia (Politeknik Negeri Bali, 2018)
Tri-Hita-Karana (THK) is one of the values of the Balinese people. It is believed that the inclusion of local culture into the language learning of Bahasa Indonesia (Indonesian) for foreign learners is not only good in enhancing students’ cultural knowledge but also in adding interest and challenge to the teaching and learning process. Appropriate teaching methods are in need to teach THK values to foreign students, so that the learners understand THK cultural values well. This study is aimed at finding the appropriate method to teach Bahasa Indonesia to foreigners with the inclusion of THK values. This study was conducted with ten foreign students who learned Bahasa Indonesia in Politeknik Negeri Bali, in 2016 Darmasiswa class. Question and observation were employed to collect the data. These methods were further complemented with participatory speaking techniques. The data collected then analyzed with coherence method. 96.7 % of the participants responded that the method used for teaching THK is very appropriate to support the process of teaching and learning of Bahasa Indonesia for foreign students. Based on the study of the responses given by the foreign learners of Bahasa Indonesia, it could be summarized that 96.7 % the respondents indicated that the methods which incorporated THK were very appropriate to support the teaching and learning process of Bahasa Indonesia for foreign students. This study also revealed that there were some methods which were more appreciated by the learners, such as: guessing pictures, running dictation, observation, video documentation, immersion, and debate. Amongst the methods, immersion was the most preferred, because through this method, learners could directly feel and experience the cultures of Balinese daily life.